Design of A Monitoring System for the Implementation of Energy Management in the Electrical Engineering Study Program Workshop of the Medan State Polytechnic - Sitepu, Trahman; Suparmono; Salman, Aulia; Hasan, Faisal Fahmi; Sofyan, Zul Fikri; Cholish; Abdullah (MultiTech Publisher, 2024)
The researcher wants to make a KWH meter monitoring tool with estimated usage costs so that the tools he makes can help the community to minimize costs in the electricity consumption area, especially in the workshop room located on the 1st floor of building C at Medan State Polytechnic. The long-term goal of this research is to develop an Internet of Things (IoT)–based KWH meter monitoring tool that can read current, voltage, frequency, power factor, and power consumption. This utilization shows the use of costs that have been incurred in real-time by displaying the results on the LCD and can also be from the user's mobile phone. In this study, the strategy used in the energy management framework was determined using SWOT analysis. From the results of the measurement and monitoring of electrical energy consumption obtained the results that, energy management is carried out by applying Standard Operating Procedures for the use of electrical energy in the electrical engineering workshop room in order to save more minimal energy consumption with a large error (Error) PZEM in measuring Voltage is 0.0198% in measuring Current is 0.612%. in measuring Cosphi is 0.01%. in measuring Frequency is 0.003%. in measuring Power is 0.183%. And the average measurement error rate is below 0.5%, namely 0.23%.